ANALISIS SARANA DAN PRASARANA SEKOLAH TERHADAP MINAT BELAJAR SISWA - Angela Aprillicia Harianja, Elsa Siburian, Fiber Yun Almanda Ginting (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research focuses on improving facilities and infrastructure in elementary schools to increase students' interest in learning. The approach used is descriptive qualitative, with data collection through observation, interviews, documentation and recording. The data collected is in the form of interview transcripts, field notes, personal documents, photos, etc. Data analysis was carried out inductively to find the meaning behind the observed data. The research results show that facilities and infrastructure are very important in supporting the teaching and learning process. The availability of adequate facilities and infrastructure can create a pleasant atmosphere for teachers and students, so that learning achievement can increase. Teachers must have creativity in creating and choosing learning media that suits students' needs, so that students are interested in learning. The use of learning applications that act as learning media is expected to increase students' interest in learning. Teachers must also have special strategies in delivering learning material so that students do not get bored and learning becomes fun. Various applications such as Quizizz, Tiktok, and Google Form are used to increase students' interest in learning.